Les appels de Margaret Fell pour convertir les Juifs : de l’émancipation à la soumission chez la première femme Quaker - Frédéric Herrmann (Anglophonia)
The aim of this paper is to examine the relationship between women and power in 17th c. England at a time of great religious conflict during the Commonwealth, the Protectorate and the Restoration, and showcased through the example of Margaret Fell, one of the very first Quaker women. Her attempts to convert the Jews to Christianity using the written word (she published several pamphlets on the subject in the 1650s and 1660s) symbolically placed her in an unprecedented position of authority and power, as they rested on the premise that women were the spiritual equals of men and could set about the task of converting the Jews as well as men could. Her status both as a woman and as a Dissenter from religious orthodoxy excluded her from power and confined her to the bottom of the patriarchal and holy hierarchy. This led her to see a likeness, even a similarity, in the plight of the Jews, which may explain why her works on the ‘Calling’ of the Jews are far more irenicist in tone and nature than those of most of her contemporaries. Yet, the full force of Fell’s rhetoric of conversion, steeped in the spiritualistic Quaker denunciation of Jewish legalism tends to mitigate this picture. Targeting those that were inferior to her in the religious and social order —the Jews—indirectly enabled Fell to affirm her newfound superiority at their expense. Here, the relative advance towards emancipation of women seems to have been possible only through the reproduction by women of the logics of male domination exerted over a third person.